Transnational connections and the Arab Gulf - Al-Rasheed, Madawi (Routledge, 2005)
This book challenges the definitions of globalisation and transnationalism as a one way process generated mainly by the Western World and the view that the latter is a twentieth century phenomenon.
Keywords: Persian Gulf States -- Civilization.; Persian Gulf Region -- Civilization.; Political culture -- Persian Gulf States.; Political culture -- Persian Gulf Region.; Group identity -- Persian Gulf States.; Group identity -- Persian Gulf Region.; Space and time -- Sociological aspects.; Identité collective -- États du golfe Persique.; Identité collective -- Persique, Région du golfe.; États du golfe Persique -- Civilisation.; HISTORY -- General.; Civilization; Group identity; Political culture; Space and time -- Sociological aspects; Persian Gulf Region; Persian Gulf States